2021
DOI: 10.1002/eap.2349
|View full text |Cite
|
Sign up to set email alerts
|

Microhabitats associated with solar energy development alter demography of two desert annuals

Abstract: Political and economic initiatives intended to increase energy production while reducing carbon emissions are driving demand for solar energy. Consequently, desert regions are now targeted for development of large-scale photovoltaic solar energy facilities. Where vegetation communities are left intact or restored within facilities, ground-mounted infrastructure may have negative impacts on desert-adapted plants because it creates novel rainfall runoff and shade conditions. We used experimental solar arrays in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 73 publications
0
7
0
Order By: Relevance
“…Several studies have found that ground-mounted solar energy, specifically PV, can impact air temperature, photosynthetically available radiation, rate of photosynthesis (Armstrong et al, 2016;Choi et al, 2020;Guoqing et al, 2021). Additionally, solar energy can impact plant diversity, abundance, and demography (Hernandez et al, 2020a;Tanner et al, 2020), and soil moisture creating unique microclimates under and around solar arrays (Tanner et al, 2020(Tanner et al, , 2021. For example, Grodsky and Hernandez (2020) found that development decisions for a 392 megawatt (MW) concentrating solar energy power plant in the Mojave Desert reduced cover and structure of desert perennial plants and their ecosystem services and facilitated the growth of invasive grass species.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have found that ground-mounted solar energy, specifically PV, can impact air temperature, photosynthetically available radiation, rate of photosynthesis (Armstrong et al, 2016;Choi et al, 2020;Guoqing et al, 2021). Additionally, solar energy can impact plant diversity, abundance, and demography (Hernandez et al, 2020a;Tanner et al, 2020), and soil moisture creating unique microclimates under and around solar arrays (Tanner et al, 2020(Tanner et al, , 2021. For example, Grodsky and Hernandez (2020) found that development decisions for a 392 megawatt (MW) concentrating solar energy power plant in the Mojave Desert reduced cover and structure of desert perennial plants and their ecosystem services and facilitated the growth of invasive grass species.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is no standard statistical approach for estimating seed mortality and germination from field experiments, and even observations from the same kind of experiment are often analyzed in disparate ways. For instance, three recent studies that used seed bag burial experiments each analyzed the observations differently: by regressing seeds in year t+1 on seeds in year t (Kurkjian et al, 2017), fitting an exponential curve (Lommen et al, 2018), or estimating the proportion of surviving seeds (Tanner et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Major knowledge gaps remain in our understanding of the relationship between solar energy infrastructure and wildlife. ,, To date, empirical research has documented direct negative impacts on biodiversity for plants and animals within large, ground-mounted facility footprints during the construction and operation of PV and concentrating solar power facilities. , Other studies have reported avian richness in large, ground-mounted solar facilities to be comparable to that of active pasture/cropland, but less than that of abandoned cropland, as well as lower species density and richness inside of large, ground-mounted solar facilities compared to that of facility boundary zones and unaltered controls. Beyond these studies, there is little data regarding other topics such as solar infrastructure’s influence on species ranges, behavior, occupancy/density, and, critically, movement. One study describes negative impacts of solar development on ungulates, including barrier effects on both resident and migratory populations as well as direct and indirect habitat loss, but more data are needed to characterize the relationship between solar energy infrastructure and animal movement.…”
Section: Introductionmentioning
confidence: 99%